A Review of PSD and Soil Classification of DMS: Characterization Challenges - Siti Farhanah, SM Johan; Chee Ming, Chan; Noor Amira, Sarani; Norazzlina, M.Sa'don; Norsuzailina, Mohamed Sutan; Abdul Razak, Abdul Karim; Faisal, Amsyar (Karya Ilham Publishing, 2025)
Dredged marine soils (DMS) are variable sediments excavated for navigation and development. Initially poor in geotechnical quality, their composition reflects diverse geological and anthropogenic influences. Dredging and pretreatment also alter particle size distribution (PSD). The Unified Soil Classification System (USCS), designed for more homogeneous soils, struggles to accurately classify complex DMS mixtures, hindering predictive capability for engineering behavior. A comprehensive characterization of DMS presents significant geotechnical challenges, particularly regarding the accurate determination of PSD and appropriate soil classification. This study synthesizes extant literature and contemporary geotechnical analyses to interpret the inherent limitations of conventional classification framework, including the USCS. Effective beneficial reuse requires moving beyond traditional classification towards comprehensive, performance-based evaluations and site-specific investigations to fully understand and utilize these complex materials.